A HIGH RESOLUTION STUDY OF FORSTERITE DISSOLUTION RATES - Rosso J.J.; Rimstidt J.D. (My University, 2000)
The rates of dissolution of olivine (Fo92) were measured over the pH range of 1.8 to 3.8 and from 25 to 45°C using an externally recycled mixed flow reactor. The data were filtered to remove several sources of systematic errors including non-steady state measurements, solution concentrations that were less than 50% above the detection limit, and Mg/Si rate ratios 40% (~3σ or 98% confidence limit) greater or smaller than 1.84, which is the stoichiometric ratio of these elements in the mineral used. The effect of random errors on calculated values of Ea and n were minimized by collecting a large amount of data. Twenty-eight different runs produced 772 rate measurements of which 284 were rejected in order to remove systematic and large random errors, leaving 488 data. The errors associated with these remaining data are normally distributed. The data were regressed to the equation log r-log A-Ea2.303R 1T -n pH to find that log A = 0.54 +/- 0.14, Ea = 42.6 +/- 0.8 kJ/mol, and n = 0.50 +/- 0.004 (R2 = 0.97).Based on these results, we postulate that the activated complex for forsterite dissolution involves a hydronium ion adsorbed to the forsterite surface in such a way that two of the three hydrogen atoms are associated with two Si-O-Mg bridging oxygen atoms. In this configuration, the adsorbed hydronium ion dissociates to form H-O-Si bonds as water molecules move from the solution to hydrate the two Mg atoms, breaking the Mg-O-Si bonds. This dissociation of the hydronium ion to form two H-O-Si groups on the forsterite surface leads to the observed reaction order for hydrogen ions of 0.5. The rate of breakdown of this activated complex is proportional to the rate at which the water molecules move from the solution to hydrate the Mg ions. Several other silicate mineral dissolution reactions, which have reaction orders of 0.5, may involve similar activated complexes.